Hydrology at Aberdeen – thinking about water locally and globally. (2nd October 2019) - Soulsby, Chris; Comte, J. C.; Geris, J.; Gibbins, C. N.; Tetzlaff, D.
ABSTRACT: Although geographical hydrology research at Aberdeen contributed significant insights into the connections between river channel processes and landscape evolution in the early twentieth century it was not until the 1980s that hydrology became a discernible research theme in the Department of Geography. Whilst the research initially focused on understanding the linkages between fluvial geomorphology, hydrology and in-stream hydraulics, since the mid-1990s a burgeoning research community has made significant contributions to advancing physical hydrology, understanding water quality issues and elucidating inter-connections between hydrology and both terrestrial and aquatic ecosystems. A particular research strength has been the use of isotopic tracers (especially high-resolution, field-based data) to advance hydrological models. Work at Aberdeen has also been internationally leading in terms of understanding the role of hydrology in shaping the life cycle of Scottish Atlantic salmon and other aquatic organisms. Ideas and research approaches developed at local Scottish field sites are being increasingly applied and adapted to advance hydrological understanding in geographical regions as diverse as the rain forests of Costa Rica, the karst of south west China, aquifers in east Africa, the Chilean high Andes, Arctic Canada, peatlands in western Siberia and forests in northern Germany.